(3EbJUGOjGJ GdehGQO hGdHjFIs - (3EjeGf YWjI(B, (3fGUas ((3GdEScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI(B,s, 2007)
(3jVe GdehGQO GdEbJUGOjI hJbSjeGJgG, GdehGQO GdWHjYjI ZjQ GdeJLOOI, CgejI GdRQGYI aj GdEbJUGOjGJ GdfGejI, GdSjGSI GdSYQjI GdRQGYjI, EbJUGOjGJ GdehGQO GdHTQjI, EbJUGOjGJ GdScGf, EbJUGOjGJ GdUfGYI, GdJdhK GdHjFjs
Keywords: (3GdHjFIs; (3GdehGQO GdEbJUGOjIs; (3GdehGQO GdWHjYjIs; (3GdehGQO(B- (3EbJUGOjGJs